2023
DOI: 10.1186/s12983-023-00494-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature and invasive alien predator on genetic and phenotypic variation in the damselfly Ischnura elegans: cross-latitude comparison

Abstract: Background Understanding and predicting how organisms respond to human-caused environmental changes has become a major concern in conservation biology. Here, we linked gene expression and phenotypic data to identify candidate genes underlying existing phenotypic trait differentiation under individual and combined environmental variables. For this purpose, we used the damselfly Ischnura elegans. Egg clutches from replicated high- (southern Sweden) and central-latitude (southern Poland) populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 81 publications
2
4
0
Order By: Relevance
“…Apart from survival, our results aligned with previous findings in I. elegans , where faster growth rate and reduced development time, as found in the non-winter cohort or when density of individual increases, often come at a cost of having a smaller mass 28 , 33 , 51 . However, previous studies tended to observe the opposite patterns with a smaller size in diapausing individuals 5 , 18 , 19 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Apart from survival, our results aligned with previous findings in I. elegans , where faster growth rate and reduced development time, as found in the non-winter cohort or when density of individual increases, often come at a cost of having a smaller mass 28 , 33 , 51 . However, previous studies tended to observe the opposite patterns with a smaller size in diapausing individuals 5 , 18 , 19 .…”
Section: Discussionsupporting
confidence: 90%
“…Our results also showed that the effects of wintering on life-history was mostly independent of the latitude, as none of our variables, except GRM, exhibited significant latitude × wintering interaction. The two latitudes differed significantly in all traits measured with faster growth and lower mass in central-latitude individuals compared to high-latitude individuals, in line with previous studies 15 , 28 . In general, the differences observed between latitudes in the non-winter cohort remained after winter diapause.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Accumulating evidence suggests that these two life stages are not independent: environmental stressors experienced during the larval stage may affect the cross‐metamorphic adult stage (Sniegula et al, 2020), and stress during the adult stage may carry over to the offspring larval stage (Rolff, 1999). The species has been the subject of intense evolutionary ecological studies on plasticity and adaptive response in the context of climate change, including evolutionary trade‐offs (Stoks & De, 2011; Wos et al, 2023), thermal adaptation (Lancaster et al, 2015, 2016; Shama et al, 2011; Tüzün & Stoks, 2022), and adaptation along environmental gradients (Dudaniec et al, 2018, 2022; Janssens et al, 2014; Raczyński et al, 2022), including urbanization (Solimini et al, 1997). As a generalist species, I. elegans represents a relatively tolerant damselfly when it comes to stressors caused by urbanization (Goertzen & Suhling, 2013; Verheyen et al, 2019; Villalobos‐Jimenez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%